Identification of a molecular defect in a stillborn fetus with perinatal lethal hypophosphatasia using a disease-associated genome sequencing approach - Olech, Ewelina M.; Zemojtel, Tomasz; Sowińska-Seidler, Anna; Robinson, Peter N.; Mundlos, Stefan; Karczewski, Marek; Jamsheer, Aleksander (Polish Journal of Pathology, 2016)
Lethal skeletal disorders represent a heterogeneous and clinically variable group of genetic conditions, usually difficult to diagnose without post-mortem radiological assessment. Here we report on a stillborn patient delivered at 22 weeks of gestation who presented with severe skeletal symptoms comprising limb shortening and intrauterine fractures detected upon prenatal ultrasound and autopsy examination. Since post-mortem X-ray was refused and no phenotypic diagnosis could be attempted, we performed next-generation sequencing (NGS) of 2741 genes associated with all known Mendelian disorders. With this strategy, we were able to demonstrate the diagnosis at a molecular level, which turned out to be perinatal lethal hypophosphatasia (HPP). This severe form of HPP represents an inborn defect of ossification often resulting in stillbirth or postnatal death. The NGS panel revealed compound heterozygous ALPL missense mutations: c.1283G>C(p.Arg428Pro) and c.1363G>A(p.Gly455Ser). Mutations detected in our case, although previously described in other patients, have not been reported to co-occur in a single individual. The diagnosis established in our index using the NGS-based approach could have been successfully reached by standard radiography. Thus, our report points to the importance of X-ray examination in stillborn cases and highlights the emerging role of NGS strategies in the diagnostic process of prenatally manifesting skeletal disorders.